The Context, Input Process, Product (CIPP) evaluation model as a Comprehensive Framework for evaluating online English learning towards the industrial revolution era 5.0 - susanto, Ferri; hamzah, Syukri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The research focuses on evaluation using qualitative descriptive evaluative methods. This evaluation research aims to determine whether online English courses are good or not in three study programs, namely Constitutional Law, Sari'a Economic Law and Islamic Family Law at Islamic University of Fatmawati Sukarno Bengkulu for the 2021-2022 period with the CIPP model (context, input, process, and product). Instrument development in this study is an instrument that uses the CIPP model based on Daniel Stufflebeam's theory. Data collection techniques using closed questionnaires and supported by triangulation, namely observation, structured interviews and documentation. Legitimacy by using Trustiness. Data management refers to the Guttmann scale. The results showed an average score of 0.70 from the context evaluation, 0.48 from the input evaluation which indicated a fairly weak average score, 0.77 from the process evaluation, and 0.785 from the product evaluation. So from the CIPP evaluation process for online learning English courses at the Fatmawati Sukarno Bengkulu State Islamic University, it is quite good.